RADIOLOGICAL DIAGNOSTICS OF BILE DUCTS CONSTRICTIVE LESIONS (REVIEW OF LITERATURE) - V. A. Malakhanov; P. V. Seliverstov (Acta Biomedica Scientifica, 2017)
Nowadays hospitals use a large number of methods of radiological diagnostics that are able not only to evaluate morphological changes of hepatobiliary zone, but also to assess functional state of the liver, and the state organ hemodynamics. Despite that, differential diagnostics of biliary tract occlusive lesions is still a challenge that requires a combination of various modern techniques. Misdiagnosis, delay in surgical treatment lead to serious complications, sometimes with fatal consequences. In this category of patients, each method of instrumental diagnostics has its advantages and disadvantages. To determine the nature of the pathological process in the majority of cases it is necessary to consistently use a wide range of diagnostic procedures. The issue of selection of optimal diagnostic algorithm for assessment of the state of hepatobiliary organs with application of new high-tech methods of radial diagnostics remains urgent. Early identification of biliary hypertension causes and the nature of the block helps to reduce the risk of serious complications, promotes the development of optimal management of patients, as well as allows to plan the type and volume of surgery.